Introduction To Basic Financial Concepts For Kindergarten Children At Tunas Kemuning Kindergarten, Kemuning Muda Village, Siak Regency - Wariam, Inge; Latifah, Anni; Indriani P, Theresia; Wahyuni, Sri; Talis, Novrida; Rasiyem, Rasiyem; Agustina, Yumniati (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Early financial literacy is an important foundation for developing financial awareness and skills. This program was carried out through the Community Service Program (KKN) at Tunas Kemuning Kindergarten, Kemuning Muda Village, in October 2024. This program aims to introduce basic financial concepts to kindergarten children and improve teacher competency in school financial management. This program uses a multi-method approach, including interviews, interactive socialization, and practical training. The program results showed that children better understood the basics of counting, saving habits, recognition of types of money, and simple financial transactions. Teachers reported increased knowledge of financial management and the ability to apply transparent bookkeeping methods. Although the results were positive, the limited time required to implement the program was a challenge that limited its impact. This program emphasizes the importance of early financial education and teacher training in financial management. Recommendations for future initiatives include extending the duration of the program, integrating financial literacy into the early childhood education curriculum, and involving parents to strengthen learning at home. The uniqueness of this program lies in its community-based approach that combines children's financial literacy education with increasing teacher capacity in financial management.